Manifestation and Elimination of â€œPackingâ€ Effect in the Media with Non-Penetrative and Penetrative Cryoprotectants - Ramazanov, V. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2009)
Erythrocyte damage under freezing with low and high hematocrits (0.8 and 40%, correspondingly) in the media with nonpenetrative polymer cryoprotectants (polyethylene glycol with m. w. of 1500 (PEG-1500), dextran) and dimethyl sulfoxide (DMSO) penetrative one, was investigated. The manifestation and elimination of the â€œpackingâ€ effect were established to be significantly dependent on cryopreservative ionic strength. Under physiological ionic strength (0.15 mol/l NaCl) for this effect manifestation it is necessary to combine PEG-1500 or dextran in 5 and 10% concentrations, correspondingly, with 5% DMSO or increase PEG-1500 or dextran number up to 10 and 15%, correspondingly. If ionic strength is lower than physiological one (0.05 mol/l NaCl), the mentioned combination of polymer cryoprotectants and DMSO is sufficient to eliminate the â€œpackingâ€ effect. However for this effect elimination under physiological ionic strength of necessity is 15% DMSO. The analysis of the obtained results and literature data enable assuming the manifestation of â€œpackingâ€ effect under rapid freeze-thawing to be determined by the stage of rapid thawing, when the increment of osmotic effect occurs due to the environment dilution with water, being initially intracellular one. Narrowing of boundaries of cell volume change during freeze-thawing cycle in the medium with penetrative and non-penetrative cryoprotectants results in resistance to the mentioned osmotic effect and â€œpackingâ€ effect elimination.